Pengaruh Model Problem Based Learning Berbantuan Media Wordwall terhadap Hasil Belajar Matematika Siswa Kelas IV SDN 26 Cakranegara - Yanti Fuspawati; Ida Ermiana; Vivi Rachmatul Hidayati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Research on the impact of the Problem-Based Learning model supported by Wordwall media on the mathematics learning outcomes of elementary school students remains limited. Low mathematics learning outcomes and suboptimal student engagement during the learning process indicate a need for an innovative learning model supported by engaging media. This study aims to determine the effect of the Problem-Based Learning model supported by Wordwall media on the mathematics learning outcomes of fourth-grade students at SDN 26 Cakranegara. The study employed a quantitative approach using a quasi-experimental design—specifically, a non-equivalent control group design. The sample consisted of 55 students: 28 students in class IV-B (experimental group) and 27 students in class IV-A (control group). Data collection techniques included tests and observations. The data underwent prerequisite testing, comprising normality and homogeneity tests. Subsequently, the data were analyzed using an independent sample t-test for hypothesis testing and an effect size test. The results showed that the average post-test score of the experimental group (83.93) was higher than that of the control group (65.63). Hypothesis testing revealed a Sig. (2-tailed) value of < 0.001, indicating a significant difference in mathematics learning outcomes between the experimental and control groups. The effect size analysis using Cohen's d yielded a value of 1.93, falling into the category of a very high effect. Based on these findings, it can be concluded that the Problem-Based Learning model supported by Wordwall media has a significant effect on the mathematics learning outcomes of fourth-grade students at SDN 26 Cakranegara.